Inactivation of the uptake hydrogenase in the purple non-sulfur photosynthetic bacterium Rubrivivax gelatinosus CBS enables a biological water–gas shift platform for H2 production. (1st July 2019) - Eckert, Carrie A; Freed, Emily; Wawrousek, Karen; Smolinski, Sharon; Yu, Jianping; Maness, Pin-Ching
Abstract: Biological H2 production has potential to address energy security and environmental concerns if produced from renewable or waste sources. The purple non-sulfur photosynthetic bacterium Rubrivivax gelatinosus CBS produces H2 while oxidizing CO, a component of synthesis gas (Syngas). CO-linked H2 production is facilitated by an energy-converting hydrogenase (Ech), while a subsequent H2 oxidation reaction is catalyzed by a membrane-bound hydrogenase (MBH). Both hydrogenases contain [NiFe] active sites requiring 6 maturation factors (HypA-F) for assembly, but it is unclear which of the two annotated sets of hyp genes are required for each in R. gelatinosus CBS. Herein, we report correlated expression of hyp1 genes with Ech genes and hyp2 expression with MBH genes. Moreover, we find that while Ech H2 evolving activity is only delayed when hyp1 is deleted, hyp2 deletion completely disrupts MBH H2 uptake, providing a platform for a biologically driven water–gas shift reaction to produce H2 from CO.